Considerations for using reproduction data in toxicokinetic–toxicodynamic modeling. (7th July 2021) - Jager, Tjalling; Trijau, Marie; Sherborne, Neil; Goussen, Benoit; Ashauer, Roman
Abstract: Toxicokinetic–toxicodynamic (TKTD) modeling is essential to make sense of the time dependence of toxic effects, and to interpret and predict consequences of time‐varying exposure. These advantages have been recognized in the regulatory arena, especially for environmental risk assessment of pesticides, where time‐varying exposure is the norm. We critically evaluate the link between the modeled variables in TKTD models and the observations from laboratory ecotoxicity tests. For the endpoint reproduction, this link is far from trivial. The relevant TKTD models for sublethal effects are based on dynamic energy budget (DEB) theory, which specifies a continuous investment flux into reproduction. In contrast, experimental tests score egg or offspring release by the mother. The link between model and data is particularly troublesome when a species reproduces in discrete clutches and, even more so, when eggs are incubated in the mother's brood pouch (and release of neonates is scored in the test). This situation is quite common among aquatic invertebrates (e.g., cladocerans, amphipods, mysids), including many popular test species. In this discussion paper, we treat these and other issues with reproduction data, reflect on their potential impact on DEB‐TKTD analysis, and provide preliminary recommendations to correct them. Both modelers and users of model results need to be aware of these complications, as ignoring them could easily lead to unnecessary failure of DEB‐TKTD models during calibration, or when validating them against independent data for other exposure scenarios. Integr Environ Assess Manag 2022;18:479–487. © 2021 SETAC KEY POINTS: Toxicokinetic‐toxicodynamic (TKTD) models are receiving increasing attention for risk assessment of pesticides; for sublethal effects, these models are based on Dynamic‐Energy Budget (DEB) theory. For reproduction, the modeled property (mass investment into reproduction) does not match what is observed in experimental tests (egg or neonate release), requiring auxiliary hypotheses. Ignoring (or incorrect) auxiliary hypotheses has the potential to bias TKTD analyses, and can lead to unnecessary failure of the analysis in a risk‐assessment context. We present and discuss these issues in detail, and provide preliminary recommendations to ensure effective application of DEB‐based TKTD models.